Tutoring as a Supportive Pillar for Improving Student Academic Performance - Božnar, Julijana; Novak, Vesna (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
A properly established tutoring system is crucial, as it is an effective form of support based on collaboration between tutors and students. The main focus is on creating a collaborative, relaxed and friendly environment, which contributes to better student cohesion, better interpersonal relationships and a greater sense of belonging, resulting in higher levels of motivation and satisfaction. In this paper, we describe a study that explored the impact of tutoring on students' academic performance, the reasons for using or not using tutoring, and students' opinions and experiences of tutoring. The results showed that tutoring has a positive impact on academic performance, with students who benefited from tutoring achieving on average one grade higher than those who did not. We also found that the majority of students have a positive opinion of tutoring, underlining its importance in students' academic and personal development.